Dental macrowear and cortical bone distribution of the Neanderthal mandible from Regourdou (Dordogne, Southwestern France). Issue 132 (July 2019) - Fiorenza, Luca; Benazzi, Stefano; Kullmer, Ottmar; Zampirolo, Giulia; Mazurier, Arnaud; Zanolli, Clément; Macchiarelli, Roberto
Abstract: Tooth wear is an important feature for reconstructing diet, food processing and cultural habits of past human populations. In particular, occlusal wear facets can be extremely useful for detecting information about diet and non-masticatory behaviors. The aim of this study is to reconstruct the diet and cultural behavior of the Neanderthal specimen Regourdou 1 (Dordogne, Southern France) from the analysis of the macrowear pattern, using the occlusal fingerprint analysis method. In addition, we have also examined whether there is any association between the observed dental macrowear and mandibular bone distribution and root dentine thickness. The posterior dentition of Regourdou 1 is characterized by an asymmetric wear pattern, with the right side significantly more worn than the left. In contrast, the left lower P3 shows a more advanced wear than the right premolar, with unusual semicircular enamel wear facets. The results from occlusal fingerprint analysis of this unique pattern suggest tooth-tool uses for daily task activities. Moreover, the left buccal aspect of the mandibular cortical bone is thicker than its right counterpart, and the left P3 has a thicker radicular dentine layer than its antimere. These results show a certain degree of asymmetry in cortical bone topography and dentine tissue that could be associated with the observed dental macrowear pattern. The molar macrowear pattern also suggests that Regourdou 1 had a mixed diet typical of those populations living in temperate deciduous woodlands and Mediterranean habitats, including animal and plant foods. Although this study is limited to one Neanderthal individual, future analyses based on a larger sample may further assist us to better understand the existing relationship between mandibular architecture, occlusal wear and the masticatory apparatus in humans.